Combined treatment using novel multifunctional MAu-GelMA hydrogel loaded with neural stem cells and electrical stimulation promotes functional recovery from spinal cord injury. Issue 12 (15th June 2023) - Kong, Weijian; Zhao, Yinlong; Xiaoyu, Yang; Chen, Jing; Chen, Yihang; Zhao, Zhengyang; Chen, Xiaonan; Wang, Feng; Fu, Chuan
Abstract: The massive death of nerve cells and the inflammatory microenvironment resulting from the release of reactive oxygen species after spinal cord injury (SCI) hinders the subsequent reconstruction of motor function. Owing to complex pathological changes, combination therapy is a potential new way to treat SCI. In this study, a novel multifunctional hydrogel containing an MXene-Au complex was constructed, and neural stem cells (NSCs) loaded in the hydrogel were combined with electrical stimulation to promote the recovery of motor function after SCI in rats. The constructed MAu-GelMA hydrogel had good reactive oxygen species-scavenging ability, electrical conductivity, and antibacterial ability. Simultaneously, electrical stimulation promoted the proliferation and differentiation of NSCs into nerve cells and promoted the establishment of synaptic connections between neurons. In the rat SCI model, combined treatment using MAu-GelMA hydrogel carrying NSCs and electrical stimulation reduced the formation of cavities and glial scars, enhanced neuronal differentiation and myelin regeneration of NSCs in the injured area, and promoted the recovery of motor function after SCI. In conclusion, in this study, we constructed a novel multifunctional hydrogel capable of carrying NSCs, which upon combining with electrical stimulation during treatment, effectively promoted the recovery of motor function in rats with SCI, thereby providing a new combination therapy strategy for SCI.